The Luminous mechanism of Eu2+ and Dy3+ co-doped long persistent luminous fiber. Issue 17 (September 2019) - Guo, Xuefeng; Zhang, Keqin; Ge, Mingqiao
Fiber-forming polymer polyethylene terephthalate chips were blended with Eu 2+ and Dy 3+ co-doped SrAl2 O4 (SAOED) to afford luminous fiber with long and persistent afterglow. A dynamical model was set up to study the afterglow process in order to correlate the afterglow characteristics with the trap levels of SAOED and luminous fiber. The results indicated that the illustration of initial afterglow for luminous fiber was obviously lower than that of SAOED, but its decay process was moderately slow and therefore longer than that of SAOED. Compared with SAOED, the thermo-luminescence peak of the fiber shifted to the higher temperature, and its intensity was lower than that of SAOED. With the time extension of delay time after excitation, the depth of trap level for luminous fiber in our studies did not show any significant change. The afterglow decay behavior can be best fit by using I = I 0 /(1 + bt ) 2 ; the fitting showed that the afterglow decay process followed the second order dynamics.